The Importance of the Index Insurance for the Development of Agricultural Insurance in Georgia - Ghutidze, Tamar (European Scientific Journal, ESJ, 2017)
Agricultural sector, unlike other sectors of the economy, is distinguished by specific risk factors, which largely depends on natural climatic conditions and the ongoing global meteorological changes. Insurance is the financial mechanism, with its considerable contribution to the country's social and economic stability. The insurance sector's prospects and problems today are vital issues for the agriculture as well as for the economy and employment. In case of Georgia, the development direction and the situation was not so successful, until 2014, the share of agricultural insurance in the insurance sector did not exceed 1%. The article discusses the importance of the index insurance for the development of agricultural insurance and the need for Government Support in its promotion. The prospects and problems of agro-insurance development have been identified on the basis of comparative analysis of the insurance policies and compensation claims, regional distribution and dynamics of recent years in Georgia. Also, based on theoretical and practical analysis the essential recommendations have been designed to eliminate them and to promote development of the agriculture insurance. As well as, an attention is paid to the inclusion and use of the type of index insurance in the Georgian agricultural insurance sector.